A review of robotics in sustainable food supply chain - Zhang, Hanwen (2021)
Explosive population growth is threatening the food security of people. In order to ensure that 10 billion people are prevented from the risk of starving by 2050, the food supply chain must shift from traditional to sustainable. This shift in production requires technological advances, and robotics, a key technology in Industry 4.0, can be effective in improving productivity and reducing waste. This research reviewed 76 papers from the perspective of the food supply chain. The research highlights the application of robotics in the food supply chain and explores the economic, social and environmental sustainability impacts of its utilisation.